2008
DOI: 10.1111/j.1600-9657.2007.00502.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a 10% carbamide peroxide bleaching agent on the phosphate concentration of tooth enamel assessed by Raman spectroscopy

Abstract: The study assessed changes in phosphate concentrations of surface enamel treated with a proprietary bleaching agent ('PEROXIDE') containing 10% carbamide peroxide over a 28-day period using Raman spectroscopy. Six non-carious human molar teeth (age range 12-21 years), extracted for orthodontic reasons, were used. From the enamel face of each half tooth, a near flat enamel section, approximately 2 x 2 mm, was cut, providing 12 specimens. Each specimen was treated with 10% carbamide peroxide for 8 h day(-1) for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 24 publications
0
32
1
5
Order By: Relevance
“…The phosphate peak at 959 cm −1 represented the hydroxyapatite (HA) of enamel, and its intensity relates to the amount of HA mineral within the scanned area [41,42]. The C O Raman peak of hydroxycarbonate apatite (HCA) layer formed on the reacted BAG particles at 1085 cm −1 clearly detectable during HCA formation [29].…”
Section: Raman Micro-spectroscopymentioning
confidence: 99%
“…The phosphate peak at 959 cm −1 represented the hydroxyapatite (HA) of enamel, and its intensity relates to the amount of HA mineral within the scanned area [41,42]. The C O Raman peak of hydroxycarbonate apatite (HCA) layer formed on the reacted BAG particles at 1085 cm −1 clearly detectable during HCA formation [29].…”
Section: Raman Micro-spectroscopymentioning
confidence: 99%
“…[11] Raman spectroscopic study showed that exposure to 10% CP for more than 7 days resulted in a signifi cant decrease in phosphate concentration in the bleached enamel. [5] On the contrary, a study did not report any mechanical, morphologic, or chemical changes following vital bleaching with CP. [12] Hence, the eff ect of bleaching on dental enamel is not yet clear and is still a controversial subject.…”
Section: Discussionmentioning
confidence: 99%
“…From dentine hydrogen peroxide reaches the pulp, where it directly activates A -δ nerves which thereby results in pain. [5] Thus, the surface morphological changes may contribute to the sensitivity associated with bleaching.…”
Section: Introductionmentioning
confidence: 99%
“…The Raman spectra of enamel represent the intensity of the signal according to the frequency, and allow comparative and quantitative analysis. 26 Some studies used Raman spectroscopy and scanning electron or atomic force microscopy together to analyze the structure of the enamel surface after tooth bleaching. 13,14 Although these studies investigated vital tooth bleaching, intracoronal bleaching was studied in the present study.…”
Section: Discussionmentioning
confidence: 99%